PEMBELAJARAN LIMIT FUNGSI ALJABAR DENGAN STRATEGI DISKUSI KELOMPOK TERINTEGRASI EKSIBISI DENGAN MODEL PIMCA - Christofora Felyciana Cindy Kamagi; Santje M. Salajang; Anekke Pesik (CV. ADIBA AISHA AMIRA, 2022)
Research on learning the limit of algebraic functions is carried out using the PIMCA model. This study aims to find out how to improve student learning outcomes in learning the limit of algebraic functions with an exhibition integrated group discussion strategy with the PIMCA model. PIMCA (Presentation, Idea Mapping, Conceptualization, and Assessment Formative) which was introduced and developed by Cosmas Poluakan. This research was conducted at the Department of Mathematics Education, Manado State University, with 21 students as respondents. From the results of data analysis, the average value of the pretest was 12.57 and the average value of the posttest was 58.57. The increase in concept understanding from Idea Mapping to Concept Maps increased by 80.71%. Student skills at the time of presentation, mastery of the material and problem solving where the average student has received a very good assessment. There is an increase in student learning outcomes. The PIMCA learning model can help students understand the correct mathematical concepts. The PIMCA learning model is a new learning model that can be used as an alternative learning model in the STEM field.